Factors Influencing the Decision of the People of Kisii Town to Consume Domestic Tourism Products - Kangu, Maureen; Kyule, Alexander Katuta; Mutinda, Bernadette (Journal of Tourism Management Research, 2019)
Kenya is naturally gifted with a variety of wildlife, spectacular scenery, renowned beaches and famous sporting activities that rely on the natural environment, in addition to a world class hospitality industry. These have contributed a lot to making tourism a major economic activity. Socio-culturally, tourism gives economic meaning to traditional wear, carvings and traditional regalia. Local entertainment is also showcased to visitors. This study aimed to determine if the promotion strategies employed by the tourism industry to encourage Kenyan citizens to visit tourist attraction sites have had an impact on local residents living far from tourist attraction sites. The specific objective was to determine the factors influencing the decisions of the people of Kisii Town to consume domestic tourism products. The target population consisted of all the 37,531 residents of Kisii Town. Five-point Likert scale questionnaires were distributed among the residents to collect primary data which was then analyzed using the Statistical Package for Social Sciences (SPSS). The study found that distance, transportation costs, and affordability, were factors that influenced the consumption of tourism products in Kisii. The study concludes that distance is one of the factors highly influencing the residents’ decision to consume domestic tourism products; therefore, the relationship between the distance from Kisii town and visits to the site was noted to be significant. The tourism industry thus needs to strike alliances with transport companies to ferry people to the sites since they may not be able to relocate the sites themselves.